Principles of landscape architecture and design of small gardens of modern hospitals in the climate of Uzbekistan - Mukhiddin Imomov Rustamovich; Jasur Berdikulov Begimovich (Research Parks Publishing LLC, 2020)
The purpose of this article is to describe the general plan of the hospital (the location of buildings, structures, sites and other devices), as well as plantations. The purpose of landscaping in the hospital. Creating a moderate microclimate and sanitary conditions for the relaxation of patients. The territory of roads, corridors and lanes that are transported to the hospital, is intended to improve the appearance of the hospital.